2016
DOI: 10.3168/jds.2015-10639
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of methionine supplementation and inclusion of hydrolyzed wheat protein in milk protein-based milk replacers on the performance of intensively fed Holstein calves

Abstract: The objectives of this study were to compare 2 milk replacers containing only milk proteins with or without supplemental Met, and to compare a milk replacer containing hydrolyzed wheat protein at 4.5% of dry matter (DM) and supplemental Lys and Met against the 2 all-milk-protein formulas, by assessing their effect on the growth performance, efficiency, and plasma urea nitrogen of pre-weaning Holstein calves. Thus, 57 Holstein calves were allotted to the following 3 treatments: (1) a skim milk plus whey protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…Inc., Cary, NC). Because of inherent variability in composition of MR with added AA (Castro et al, 2016;Vasquez et al, 2017), we tested the AA composition among treatments by conducting an ANOVA using the GLM procedure in SAS, with sample considered the experimental unit. The Tukey adjustment was used to determine the differences among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Inc., Cary, NC). Because of inherent variability in composition of MR with added AA (Castro et al, 2016;Vasquez et al, 2017), we tested the AA composition among treatments by conducting an ANOVA using the GLM procedure in SAS, with sample considered the experimental unit. The Tukey adjustment was used to determine the differences among treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, bovine milk is considered to be the standard for feeding dairy cattle 1 and before 1956, whole milk was the main feed for calves 2 . Due to the increasing demand for dairy products, many dairy cattle farms started feeding calves with commercial milk replacers (MRs) 3 .…”
Section: Introductionmentioning
confidence: 99%
“…According to data observed in the present study, the Met + Cys concentration in WM (4.04 g/100 g of CP) is below the optimal level observed for best calf performance (4.4 g/100 g of CP). Consequently, Met + Cys are actually low in milk proteins, as proposed by Hill et al (2008) and Castro et al (2016), even WM being considered the best protein and energy source for calves. In addition, it is worth noting that the MR used in this study is even poorer in Met + Cys (2.8 g/100 g of CP); therefore, we suggest that companies that produce MR should add crystalline Met to their products, thereby ensuring a qualitatively higher Met + Cys product for calves' best performance.…”
Section: Body Compositionmentioning
confidence: 98%
“…Milk is considered the best protein source for young calves due to its high digestibility and balanced AA profile (Huang et al, 2015;Castro et al, 2016). However, only few studies have suggested modifications of the AA profile of liquid diets for dairy calves to promote greater performance (Hill et al, 2008;Wang et al, 2012;Hill et al, 2016).…”
Section: Introductionmentioning
confidence: 99%